Method for the biosynthesis of glutamic acid - Saari, Nazamid; Zareian, Mohsen; Ebrahimpour, Afshin (2013)
The present invention pertains to a process for production of glutamic acid and/or Y-amino butyric acid (GABA) with a Lactobacillus plantarum strain that was specifically isolated for high yield production. The method of the invention provides ideal culture condition for the production of glutamic acid and/or y-amino butyric acid (GABA). The method is specifically useful for the fermentation of foods.